Integrated genomic and transcriptomic analysis of human brain metastases identifies alterations of potential clinical significance. Issue 3 (19th August 2015) - Saunus, Jodi M; Quinn, Michael CJ; Patch, Ann‐Marie; Pearson, John V; Bailey, Peter J; Nones, Katia; McCart Reed, Amy E; Miller, David; Wilson, Peter J; Al‐Ejeh, Fares; Mariasegaram, Mythily; Lau, Queenie; et al.
Abstract Treatment options for patients with brain metastases (BMs) have limited efficacy and the mortality rate is virtually 100%. Targeted therapy is critically under‐utilized, and our understanding of mechanisms underpinning metastatic outgrowth in the brain is limited. To address these deficiencies, we investigated the genomic and transcriptomic landscapes of 36 BMs from breast, lung, melanoma and oesophageal cancers, using DNA copy‐number analysis and exome‐ and RNA‐sequencing. The key findings were as follows. (a) Identification of novel candidates with possible roles in BM development, including the significantly mutated genes DSC2, ST7, PIK3R1 and SMC5, and the DNA repair, ERBB–HER signalling, axon guidance and protein kinase‐A signalling pathways. (b) Mutational signature analysis was applied to successfully identify the primary cancer type for two BMs with unknown origins. (c) Actionable genomic alterations were identified in 31/36 BMs (86%); in one case we retrospectively identified ERBB2 amplification representing apparent HER2 status conversion, then confirmed progressive enrichment for HER2‐positivity across four consecutive metastatic deposits by IHC and SISH, resulting in the deployment of HER2‐targeted therapy for the patient. (d) In the ERBB/HER pathway, ERBB2 expression correlated with ERBB3 (r2 = 0.496; p < 0.0001) and HER3 and HER4 were frequently activated in an independent cohort of 167 archival BM from seven primary cancer types: 57.6% and 52.6% of cases were phospho‐HER3Y1222 or phospho‐HER4Y1162 membrane‐positive, respectively. The HER3 ligands NRG1/2 were barely detectable by RNAseq, with NRG1 (8p12) genomic loss in 63.6% breast cancer‐BMs, suggesting a microenvironmental source of ligand. In summary, this is the first study to characterize the genomic landscapes of BM. The data revealed novel candidates, potential clinical applications for genomic profiling of resectable BMs, and highlighted the possibility of therapeutically targeting HER3, which is broadly over‐expressed and activated in BMs, independent of primary site and systemic therapy. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.